Refractive index of ferromagnetic semiconductors in a field of coherent light beams - Semchuk, O.Yu.; Semioshko, V.N.; Bila, R.V.; Magnus Willander; Magnus Karlsteen (Functional Materials, 2004)
The influence of intense laser radiation (coherent light beams (CLB)) on refractive index of a ferromagnetic semiconductor (FMSC) has been considered. It is shown that under CLB, in FMSC the grating of a refractive index takes place. A model explaining this effect is proposed. The relevant theoretical calculations have been carried out confirming the new phenomenon, appearance of refractive index grating in FMSC in a field of CLB.